Applying Public Health Principles to Better Manage the COVID-19 Pandemic: "Community Participation, " "Equity, " and "Cultural Sensitivity". (November 2021) - Mahmood, Mohammad Afzal; Khan, Kausar Saeed; Moss, John Robert
Although coronavirus vaccine roll-out is beginning, standard public health practices will, for most people, remain their first line of protection for some time. Three principles guiding the pandemic control process, namely community participation, promotion of equity, and cultural sensitivity, can help people adhere to public health advice. These three principles can enhance intervention effectiveness, decreasing the rate of infection and protecting human rights, promoting social harmony and preventing unrest.